Nitrogen effluents from mine sites in northern Sweden : nitrogen transformations and limiting nutrient in receiving waters - Chlot, Sara (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2011)
Process water discharged from mine sites may contain elevated concentrations of nitrogen (N) and phosphorus (P), which both are nutrients for algae and aquatic plants. Thus, discharge of nutrient rich mine water can result in algal blooms, eutrophication, oxygen deficiency and changed species composition in the receiving waters. This thesis is focused on the speciation and transformation processes of N and N:P ratios in streams and lakes receiving mine effluents from the Kiruna and Boliden mine sites. In this work, a dynamic biogeochemical model was developed for the clarification pond receiving ammonium-rich mine effluents from the Boliden concentration plant. A number of such models have been developed that simulate N transformations in wastewater stabilization ponds. However, few biogeochemical models have been developed that primarily focus on simulation of processes regulating transport and removal of N in waters receiving mine effluents. The presented model calculates concentrations of six N species and simulates the rate of 16 N transformation processes occurring in the water column and sediment as well as water-sediment and water-atmosphere interactions. A six-year simulation of ammonium concentrations showed stable behaviour over time, and the calibrated model rendered coefficients of determination (R2) of 0.93, 0.79 and 0.86 for the inorganic nitrogen species ammonium, nitrate and organic nitrogen, respectively. This indicates a stable model behaviour. The simulated denitrification rate was on average five times higher than the ammonia volatilization rate, and about three times higher than the permanent burial of sedimentary nitrogen. Hence, denitrification was the most important process for the permanent removal of N. The model can be used to simulate possible measures to reduce the N load and, after some modification and recalibration, it can be applied at other mine sites affected by N-rich effluents. In addition, it was investigated which nutrient that limits bioproduction in the two aquatic ...